(untitled) (International Journal of Scientific Trends, 2025)
A word or term may be able to be different in meaning as synonyms, homonyms, antonyms and other types of formation representing the meaning of words in one of the fields of expertise. However, a word as synonym can be used in special field. There are some discussions among linguists that their idea according to representing synonyms in the technical field is limited and it is hard to find noun function synonyms in the industrial field. Terminologists look through dictionaries, books, literature, spoken contexts, printed contexts synonyms, antonyms, and homonyms occasionally in order to define exact meaning of the terminology using in the field of industry.